Relational Discipleship in a Disruptive Era: Empowering the Young Generation to Navigate Moral Challenges - Saptorini, Sari; Suryadi, Devina Herfiantika; Arifianto, Yonatan Alex (Sekolah Tinggi Agama Kristen Diaspora Wamena, 2025)
This journal article explores the concept of relational discipleship as a vital approach for empowering the younger generation to navigate the challenges posed by the era of disruption. Characterized by rapid technological advancements and significant shifts in social dynamics, this era presents numerous obstacles, including moral decline, identity crises, and negative behaviors linked to excessive technology use. The article emphasizes the importance of relational discipleship, which fosters intimate relationships between leaders and youth, facilitating spiritual growth and resilience. By implementing practical strategies such as modeling behavior, encouraging open dialogue, and involving youth in ministry leaders can effectively guide young individuals toward spiritual maturity and adherence to the truths of God's Word. Ultimately, relational discipleship emerges as a crucial means for equipping the younger generation to face the complexities of contemporary life with wisdom and grace, enabling them to embody the values of faith and integrity in a disruptive world.